2017
DOI: 10.1515/amm-2017-0256
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Heat Input on the Mechanical and Metallurgical Characteristics of Tig Welded Incoloy 800Ht Joints

Abstract: This study focuses on the effect of heat input on the quality characteristics of tungsten inert arc gas welded incoloy 800HT joints using inconel-82 filler wire. Butt welding was done on specimens with four different heat inputs by varying the process parameters like welding current and speed. The result indicated that higher heat input levels has led to the formation of coarser grain structure, reduced mechanical properties and sensitization issues on the weldments. The formation of titanium nitrides provided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Incoloy-800HT is a variation of Incoloy-800 and 800H. Alloy 800HT is an iron-nickelchromium solid-solution strengthened alloy, one of the featured materials for fourth generation nuclear power plant, with the properties of good resistance to corrosion, oxidation, and appreciable strength at high temperatures [4]. Alloy 800HT can be used as for control rod sheath materials for very-high-temperature reactor and in industrial heating equipment, hydrocarbon processing industry etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Incoloy-800HT is a variation of Incoloy-800 and 800H. Alloy 800HT is an iron-nickelchromium solid-solution strengthened alloy, one of the featured materials for fourth generation nuclear power plant, with the properties of good resistance to corrosion, oxidation, and appreciable strength at high temperatures [4]. Alloy 800HT can be used as for control rod sheath materials for very-high-temperature reactor and in industrial heating equipment, hydrocarbon processing industry etc.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies about alloys for different purposes were reported before [6][7][8][9][10][11][12][13][14]. Among the alloys, Ni-based alloys, Inconel-617 and Incoloy-800HT, were also studied by many researchers previously [1,4,[15][16][17][18][19][20]. The researches were generally focused on the oxidation behaviors in different environments, mechanical, metallurgical and tensile properties of the alloys 617 and 800HT.…”
Section: Introductionmentioning
confidence: 99%